Value-added information in term structure: the case of Malaysian government securities - Elshareif, Elgilani Eltahir; Yusop, Zulkornain; Tan, Hui Boon (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
This study empirically examines the impact of value-added information in the risk premium on the predictability of longer maturity term structure about future short-term rates in Malaysian fixed income securities market. Regardless of the absence of a time-varying risk premium in the interest rate, the Generalized Method of Moment (GMM) results suggest that there is statistical evidence to support that the longer-term spread between long-term and short-term rates does have some significant power in predicting the changes in expected future short-term rate. This implies the stability of the short-term interest rates in Malaysia.